Effect of Ammonia Fumigation Treatment on Wood Color and Chemical Composition - Weigang Zhang; Minzhen Bao; Weisheng Sun; Lei Huang; Liang Cheng (International Journal of Polymer Science)
Betula alnoides was used as a test material to study the effect of ammonia fumigation treatment on wood color and chemical composition. The effects of concentration, temperature, and duration of ammonia fumigation on wood color were studied. The properties of the material were studied using contact angle measurements, X-ray diffraction, Fourier-transform infrared spectroscopy, and dynamic thermomechanical analysis. In general, the color difference of the wood increased with the concentration of ammonia used in the fumigation process, treatment temperature, and treatment duration. After ammonia fumigation treatment, the chemical composition of hydroxyl and carboxyl groups in the wood was reduced. We concluded that ammonia fumigation treatment decreased material wettability and dynamic mechanical rigidity and increased the degree of crystallinity in wood.